Tolnaftate inhibits ergosterol production and impacts cell viability of Leishmania sp. - Yamamoto, Eduardo Seiji; de Jesus, Jéssica Adriana; Bezerra-Souza, Adriana; Brito, Juliana R.; Lago, João Henrique G.; Laurenti, Márcia Dalastra; Passero, Luiz Felipe Domingues [UNESP] (Elsevier, 2020)
Leishmaniasis is an infectious disease caused by protozoan parasites of the genus Leishmania. The treatment of all forms of leishmaniasis relies on first-line drug, pentavalent antimonial, and in cases of drug failure, the second-line drug amphotericin B has been used. Besides the high toxicity of drugs, parasites can be resistant to antimonial in some areas of the World, making it necessary to perform further studies for the characterization of new antileishmanial agents. Thus, the aim of the present work was to evaluate the leishmanicidal activity of tolnaftate, a selective reversible and non-competitive inhibitor of the fungal enzyme squalene epoxidase, which is involved in the biosynthesis of ergosterol, essential to maintain membrane physiology in fungi as well as trypanosomatids. Tolnaftate eliminated promastigote forms of L. (L.) amazonensis, L. (V.) braziliensis and L. (L.) infantum (EC50 ~ 10 μg/mL and SI ~ 20 for all leishmanial species), and intracellular amastigote forms of all studied species (EC50 ~ 23 μg/mL in infections caused by dermatotropic species; and 11.7 μg/mL in infection caused by viscerotropic species) with high selectivity toward parasites [SI ~ 8 in infections caused by dermatotropic species and 17.4 for viscerotropic specie]. Promastigote forms of L. (L.) amazonensis treated with the EC50 of tolnaftate displayed morphological and physiological changes in the mitochondria and cell membrane. Additionally, promastigote forms treated with tolnaftate EC50 reduced the level of ergosterol by 5.6 times in comparison to the control parasites. Altogether, these results suggest that tolnaftate has leishmanicidal activity towards Leishmania sp., is selective, affects the cell membrane and mitochondria of parasites and, moreover, inhibits ergosterol production in L. (L.) amazonensis.
Keywords: Anti-fungal drug; Cell membrane; Drug repurposing; Ergosterol; Mechanism of action; Mitochondria; New World Leishmaniasis; Tolnaftate